Autoecologia do camorim, Centropomus undecimalis (Bloch, 1792), (Perciformes: Centropomidae) em ambiente hipersalino em Galinhos, RN, Brasil - Mendonça, Maisa Clari Farias Barbalho de (2004)
Studies were done with the objective of knowing more about the ecology of the species Centropomus undecimalis (Bloch, 1792), regarding the aspects of population dynamics, age and growth, alimentary diet and reproduction. 1179 specimens (1122 males and 57 females), were captured in the Diamante Branco salt mine, Galinhos RN, the capture period happened between February 2001 and January 2003. Every month captures were done with the aid of fishing gears, looking for a representative sample of the population. The population dynamics showed a significant difference between the monthly relative frequencies distribution and for length classes, for males and females; and the same behavior occurred with the total weight distribution classes. The sexual proportion showed the prevalence of males during the whole period; being verified in the distribution by classes of length that there was an inversion among the sexes, the males pondered in classes of smaller length and the females in the classes of larger length. The growth parameters were obtained through the method of back calculation, being verified a low growth tax (K) and a high value of the asymptotic length. The analysis of the repletion Index and the medium repletion degree showed the prevalence of stomachs empty in the whole study period; the analysis of stomach content using the Index of Relative Importance and the alimentary Index revealed that the species is carnivore, with a tendency of piscivorous, with fishes, crustaceans, mollusks and insects in the diet. The Centropomus undecimalis reproduction was established using histological cuts, characterizing the stadiums of gonadal development for males and females. The oocyte and spermatogenic development observed allow inferring that the species is protandric hermaphrodite, through the simultaneous presence of spermatogenic tissues remains and ovarian tissues in development.